2004
DOI: 10.1038/sj.ejhg.5201186
|View full text |Cite
|
Sign up to set email alerts
|

A susceptibility gene for premature ovarian failure (POF) maps to proximal Xq28

Abstract: Terminal deletions of the long arm of the human X chromosome have been described in women with premature ovarian failure (POF). We report here the molecular characterization of an inherited deletion in two affected women and in their mother. The two daughters presented secondary amenorrhea at 17 or 22 years respectively, while the mother was fertile. She had four children, but she eventually had premature menopause at 43 years of age. The fine molecular analysis of the deletion showed that the three women carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 24 publications
3
40
0
3
Order By: Relevance
“…4). Besides these critical region, breakpoints in Xq13-Xq27 due to balanced X, autosome translocation has been reported in cases of POF [32,33,35].…”
Section: Discussionmentioning
confidence: 99%
“…4). Besides these critical region, breakpoints in Xq13-Xq27 due to balanced X, autosome translocation has been reported in cases of POF [32,33,35].…”
Section: Discussionmentioning
confidence: 99%
“…There has not been any LOH or MSI data for any of these four markers in the literature, although Xq28 has been reported to be associated with cancers in reproductive organs including the prostate, ovary and breast. [22][23][24][25] The fact that all 29 cases of ovarian cancer studied show at least one genetic alteration, either LOH or MSI, in at least one of the four microsatellite markers indicates that Xq28 may be highly relevant to ovarian cancer and that QM locus falls in a high LOH and MSI region. We have recently shown that the decrease in QM protein level, determined by immunohistochemistry, is associated with tumor grade of prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
“…As deleções parciais do cromossomo X têm sido relatadas, sendo a maioria de casos isolados com herança familiar 3,4,6,8,13 . Nos casos descritos a ausência de história familiar de menopausa precoce parece indicar que se tratem de deleções de novo do cromossomo X, embora não tenha sido realizada a investigação genética dos pais das pacientes.…”
Section: Discussionunclassified
“…Isto foi sugerido em relato de deleção na região Xq28 no qual três mulheres de uma mesma família (mãe e duas fi lhas) apresentavam diferentes genótipos, apesar de serem afetadas por alteração genética idêntica. Neste relato a mãe teve menopausa prematura aos 43 anos, ao passo que as fi lhas entraram em amenorréia secundária aos 17 e 22 anos de idade 13 . Outro estudo também achou comportamento semelhante em mãe com menopausa precoce e fi lha com FOP, ambas com deleções em Xq26.2-q28 7 .…”
Section: Discussionunclassified